INTELLECTUAL CAPITAL AND INTERNAL AUDIT PERFORMANCE: THE MINISTRY OF FINANCE'S INSPECTORATE GENERAL AUDITOR CASE - Amrie Firmansyah; Lutfi Abdul Khakim; Azkalina Diazani (Polytechnic of State Finance STAN, 2023)
This research aims to determine the influence of intellectual capital, which comprises public human capital, public organizational capital, and relational public capital, on internal auditor performance. It follows a quantitative research approach where data was collected from questionnaire surveys to 40 Inspectorate General of the Ministry of Finance auditors. Structural Equation Modeling (SEM) was employed to test the hypothesis. This research concludes that public human capital and relational public capital are positively associated with internal auditor performance. Meanwhile, public organizational capital is not associated with internal auditor performance. This research offers valuable insights into the role of intellectual capital in enhancing performance within public sector organizations.